AKIBAT PERUBAHAN REGULASI TERHADAP STRATEGI OPERASI ANTI TERORISME YANG DILAKUKAN OLEH UNIT GEGANA BRIMOB POLRI DI SUMATERA UTARA - Boy Agus Chain Gulo (YAPEKAM, 2025)
The regulatory change brought about by Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism has had a significant impact on the operational strategies employed by the Gegana Unit of the Indonesian Police Mobile Brigade (Brimob), particularly in the North Sumatra region. The background of this research stems from the growing complexity of terrorism threats and the need to adjust operational procedures to align with the new regulation, which grants broader authority to security force. This study aims to analyze the impact of the regulatory changes on the counter-terrorism operational strategies implemented by the Gegana Brimob Unit in North Sumatra, identify challenges in the strategy’s implementation, and formulate strategic solutions to enhance operational effectiveness. A descriptive qualitative approach was used, employing data collection techniques such as in-depth interviews, document analysis, and observation. The findings reveal that the regulatory change provides a stronger legal foundation and promotes a transformation in strategy from reactive to more proactive and preventive approaches. The Gegana Unit is now not only focused on enforcement but also actively engaged in prevention efforts, public education, and deradicalization programs. However, the implementation of these strategies faces several challenges, including limited human resources and logistics, suboptimal interagency coordination, and the diverse socio-cultural dynamics of the community. Therefore, recommendations to improve operational effectiveness include enhancing personnel capacity, modernizing equipment, establishing cross-sectoral standard operating procedures (SOPs), and strengthening community engagement.